(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the process of borrowing foreign words in the Russian language, its causes, features and consequences. The positive and negative aspects of borrowings, their influence on vocabulary, grammar and syntax are analyzed. Particular attention is paid to modern borrowings related to the development of technology, business and youth slang.